Islamic Psychology: An Integrative Approach to Human Behavior and Mental Well-Being - Sumaia Almajri; Najah Baroud; Khuloud Mustafa Alouzi; Amaal Kasheem (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
Islamic Psychology is an emerging field that integrates Islamic principles with psychological theories to offer a holistic understanding of human behavior and mental well-being. This paper explores Islamic psychology's foundations, key concepts, and practical applications in contemporary psychological practice. It highlights how Islamic teachings on the soul (nafs), intellect (‘aql), and heart (qalb) contribute to psychological healing, emphasizing the role of faith, spirituality, and ethical conduct in mental health. By integrating traditional Islamic knowledge with modern psychological research, Islamic Psychology provides a culturally and spiritually relevant framework for Muslim individuals and communities worldwide.